2022
DOI: 10.1186/s13584-022-00522-z
|View full text |Cite
|
Sign up to set email alerts
|

Transgender men's preferences when choosing obstetricians and gynecologists

Abstract: Background Transgender men are a marginalized population with unique health care needs. However, their usage of health services is low because of considerable discrimination. A major factor in their avoidance is patient-provider interactions. Methods This cross-sectional study included 102 transgender men who anonymously completed a 55-item questionnaire in clinic, between 10/2017 and 01/2019. In addition, 92 transgender women filled out the part a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 54 publications
(82 reference statements)
0
3
0
Order By: Relevance
“…The ability to create such relations was enhanced when women had an accompanying person -typically a professional or a volunteer -especially when these were continuous relationships of trust. In contrast, as previously demonstrated in relation to other marginalized population in Israel, such as transgenders, discrimination and negative experiences in encountering healthcare providers may impair future healthcare utilization [27].…”
Section: Discussion and Recommendationsmentioning
confidence: 71%
“…The ability to create such relations was enhanced when women had an accompanying person -typically a professional or a volunteer -especially when these were continuous relationships of trust. In contrast, as previously demonstrated in relation to other marginalized population in Israel, such as transgenders, discrimination and negative experiences in encountering healthcare providers may impair future healthcare utilization [27].…”
Section: Discussion and Recommendationsmentioning
confidence: 71%
“…5 A study from Israel on transgender population showed that some of the factors influencing TGP in approaching doctors include their knowledge, experience and ability to be gender tolerant. 6 It is important to know when and who should treat people with gender dysphoria and what referral system exists for the same. The management of TGP is interdisciplinary involving various medical personnel like the general practitioners, endocrinologists, gynaecologists, plastic surgeons, psychiatrists, speech therapists, urologists, dermatologists etc.…”
Section: Discussionmentioning
confidence: 99%
“…16 Many educational materials and guidance are available to help the interested residents and the same can be utilized to upgrade the curriculum in TGP care. 3,5,6 These curriculum improvements should be constantly evolving and may help the residents to be comfortable to start consultation with TGP and address their concerns confidently and competently while understanding their unique needs at every step of consultation. Conducting further research on best practices in transgender related care and reflective practice would be helpful to identify and promote lasting structural changes.…”
Section: Discussionmentioning
confidence: 99%